Studi Deskriptif Penerapan Alat Musik Pianika Pada Mata Pelajaran Seni Budaya dan Keterampilan (SBK) Siswa Kelas V SDN 35 Kota Bengkulu - Tarmizi, Pebrian; Hasnawati, Hasnawati; Manurung, Ingrith Carolina (UNIB Press, 2019)
This research aims to describe the application of pianika musical instruments to the learning outcomes of fifth grade students of Elementary School 35 Bengkulu City. This type of research is qualitative research. The research method is descriptive. The research instrument uses observation sheets carried out in the class by describing the results of observations. Besides observation there are also unstructured interviews and documentation. The sample in this study were students of Grade V-A Elementary School 35 Bengkulu City, which was one local or one class through the learning outcomes obtained from both cognitive, affective and psychomotor. Where the presentation of data uses data analysis techniques that include: data reduction, data display, and conclusion drawing / verification. From this research, it was found that the application of pianika musical instruments was very effective in learning Arts and Skills. Of the 30 students, 12 people got good learning outcomes. Where the 12 students understood the pianika playing technique. How to play pianika include how to hold; How to Blow; Runaway; and the Tone / Solmization Region. Furthermore, this study looked at how students play pianika in accordance with the techniques taught, so that the results obtained from 30 people who became the object of this research netted 12 students with grades in the range 12-16. Students who reached this value limit can be said to succeed in 12 people and students who scored below that standard still did not succeed at 18 people.